The effects of stacking configuration on the response of tensile and quasi-static penetration to woven kenaf/glass hybrid composite metal laminate - Dhar Malingam, Sivakumar; Subramaniam, Kathiravan; Ng, Lin Feng; Bapokutty, Omar (John Wiley and Sons Inc., 2019)
The hybridization of natural and synthetic fibers in composite materials has gained the attention in the research field due to environmental awareness. Therefore, this study focuses on the effects of fiber stacking configuration on the tensile and quasi-static penetration of kenaf/glass hybrid fiber metal laminates (FMLs). Kenaf/glass reinforced polypropylene FMLs with two different hybrid stacking configurations were prepared using hot compression process. Non-hybrid kenaf and glass fiber reinforced metal laminates were also prepared for comparison. The tensile test was conducted according to ASTM E8, while the quasi-static penetration test was carried out in accordance with ASTM D 6264 using 12.7 and 20 mm hemispherical indenters. The fractured surface of FMLs due to tensile loading was examined using scanning electron microscope, while optical micrograph was used to investigate the failure mechanism of quasi-statically penetrated laminates. From the results, FMLs with the glass plies at the outer layers of composite (H1) showed a positive hybrid effect as they displayed better tensile and penetration resistance, compared to the non-hybrid kenaf and glass reinforced FMLs. Furthermore, it could be seen that the overall performance of FMLs decreased as the kenaf content in the laminates further increases for hybrid FML.